Pengaruh Social Media Marketing dan Brand Popularity terhadap Brand Trust dan Dampaknya terhadap Purchase Intention pada Produk Skincare Hanasui di TikTok Shop - Dian Nirmalasari; Terrylina Arvinta Monoarfa; Daru Putri Kusumaningtyas (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to examine the influence of social media marketing and brand popularity on brand trust, as well as their impact on purchase intention for Hanasui skincare products on TikTok Shop. This study employs a quantitative approach using a survey method. The data collected consists of primary data obtained by distributing questionnaires to consumers who have used Hanasui skincare products on TikTok Shop. The population for this study comprises consumers of Hanasui skincare products in the Greater Jakarta area. The population for this study consisted of consumers of Hanasui skincare products in the Greater Jakarta area. The sampling technique employed was purposive sampling, with a sample size of 200 respondents who met the study criteria. Data analysis was carried out using Structural Equation Modelling (SEM) with the aid of AMOS software. The research findings indicate that social media marketing has a positive and significant effect on brand popularity. Furthermore, social media marketing and brand popularity also have a positive and significant effect on brand trust. Moreover, brand trust was found to have a positive and significant effect on purchase intention for Hanasui skincare products on TikTok Shop. It is hoped that the findings of this study will serve as a guide for companies in designing more effective digital marketing strategies by optimizing social media activities and strengthening brand popularity, thereby boosting consumer confidence and driving an increase in purchase intent for local skincare products on TikTok Shop.